Mitos Politik Aliran dan Aspirasi Politik ICMI Modernis - Saiful Mujani (Studia Islamika, 1995)
This article is a review of the writings of Adam Schwarz, titled Islam: Coming in from the Cold in his book, A Nation in Waiting, Indonesia in the 1990's. Adam Schwarz is a reporter Far Eastern Economic Review magazine published in Hong Kong. This book is the result of observations during which he served in Indonesia in the late 80s and early 90s, a period characterized much debate about Islam in Indonesia.Started writing this, Schwarz explained about the relationship Abdurrahman Wahid (Gus Dur) with the government. A few weeks after Gus Dur Tabligh Akbar held in Senayan East Parking Lot, he was "invited" Let. Colonel Prabowo, Suharto's son-president, to meet him. Reportedly, during the meeting, Prabowo warned that steps Gus Dur (with the Tabligh Akbar) has crossed the line. If he continues to play politics, said Prabowo, the first to be disturbed is president Suharto's re-election as president for the next term.DOI: 10.15408/sdi.v2i1.847